POLICY IMPLEMENTATION HOSPITAL MANAGEMENT INFORMATION SYSTEM (SIMRS) AT THE KABELOTA REGIONAL GENERAL HOSPITAL - Syavira Andina Anjar; Syahruddin Hattab; Vidyanto (RADJA PUBLIKA, 2024)
This study aims to find out and analyze the implementation of the Hospital Management Information System (SIMRS) policy at the Kabelota Regional General Hospital (RSUD) of Donggala Regency in 2024. Research Method: This study uses a qualitative approach with primary and secondary data types. Data collection techniques include in-depth interviews, observations, and documentation studies. Informants are selected purposively, including medical staff, non-medical, and technical personnel who are directly involved in SIMRS operations. Data analysis uses the Miles and Huberman interactive model, including the stages of data condensation, data presentation, and conclusion / verification as well as Analysis of Strengths, Weaknesses, Opportunities, and Threats (SWOT) The results of the research, the implementation of the SIMRS policy at Kabelota Donggala Hospital as a whole has been running well, but it has not been fully optimal. Aspects of communication, disposition/attitude, and bureaucratic structure showed positive results. However, there are significant challenges, such as internet network instability, hardware limitations, and lack of advanced training for staff. The IFAS and EFAS analysis placed hospitals in Quadrant I (Aggressive Strategy), indicating that hospitals have opportunities to leverage external factors to improve internal weaknesses and strengthen existing strengths. In conclusion, With the improvement of technological infrastructure, recruitment of additional IT personnel, and continuous training, the implementation of SIMRS at Kabelota Donggala Hospital can be optimized to support more efficient and quality health services.